Perlindungan Hukum Terhadap Pemohon Akibat Tidak Diterapkannya Asas Contradictoire Delimitatie Dalam Pendaftaran Tanah Pertama Kali Guna Pensertipikatan Tanah - Musfitha, Andi; Marniati, Felicitas Sri; Widyanti, Amelia Nur (DAS Institute, 2025)
This study analyzes the legal consequences of not applying the contradictory delimitation principle in the initial land registration process for land certification. This principle is essential to ensure clear land boundaries and prevent future disputes. The absence of this principle can lead to legal uncertainty, defects in land certificates, and boundary disputes, such as overlapping or duplicate certificates. This research employs a normative juridical approach with case analysis. The findings indicate that consistent application of the contradictory delimitation principle can protect land applicants, prevent disputes, and ensure legal certainty. As a form of legal protection, the National Land Agency (BPN) is responsible for re-measuring, restoring land boundaries, and compensating affected parties. The study recommends implementing the contradictory delimitation principle in all stages of land registration to minimize future conflicts.